Peranan Kepemimpinan Terhadap Kinerja Dengan Motivasi Kerja Dan Komitmen Organisasional Sebagai Variabel Intervening Pada “Abdi Dalem” Kadipaten Pakualaman Yogyakarta - R. Jati Nurcahyo - AKPAR BSI Yogyakarta (Universitas Bina Sarana Informatika, 2016)
ABSTRACT - This research discusses the influence of Leadership on work performance with Organizational Commitment and Work Motivation as the intervening variabels of “abdi dalem” in Kadipaten Pakualaman Yogyakarta. The objective of this research is to find out how far Leadership, Organizational Commitment, and Work Motivation influence the Work Performance of “abdi dalem”, both directly and indirectly. The research methods used are Multiple Regression Analysis and Path Analysis. The findings of the research show that Leadership - either directly or indirectly; that is through Work Motivation - influences positively and significantly to the work performane of “abdi dalem”. The research findings also show that Leadership does not have significant influence on the performance of “abdi dalem”. On the other hand, Leadership - together with Organizational Commitment and Work Motivation- has positive and significant influences on the work performance of “abdi dalem”. Specifically, Leadership directly has greater influence compared to Organizational Commitment and Work Motivation on the work performance of “abdi dalem” in Kadipaten Pakualaman Yogyakarta. Keywords : Leadership, Organizational Commitment, Work Motivation and Work Performance. ABSTRAK - Penelitian ini membahas pengaruh Kepemimpinan terhadap kinerja kerja dengan Komitmen Organisasi dan Motivasi Kerja sebagai variabel intervening dari